Pengaruh Pemberian Pupuk Kandang Ayam dan Pupuk Urea Terhadap Pertumbuhan Sawi (Brassica Juncea L.) dengan Menggunakan Batang Pisang - Edi Indra Gunawan; Yudi Triyanto; Kamsia Dorliana Sitanggang (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2021)
This study aims to determine the effect of chicken manure and urea fertilizer on the growth of mustard greens (Brassica juncea L.) using banana stems. Mustard greens are one of the vegetables that contain various kinds of vitamins and minerals that are good for health. The demand for mustard plants increases along with the increase in population and nutritional needs. Design This experimental research was conducted by using a factorial completely randomized design (CRD) with a test pattern consisting of 2 factorials. Factorial I was a type of chicken manure with 2 replications, namely the first dose of 10 grams / hole and the second dose of 20 grams / hole. The second factor was urea fertilizer with 2 replications, namely the first dose of 5 grams / hole and the second dose of 10 grams / banana stem. The data obtained were analyzed by Microsoft Excel. Parameters include: number of leaves, leaf height, leaf area, wet weight of mustard greens (Brassica juncea L.). The results of the research that have been done show that the optimal fertilizer used is chicken manure with a dose of 20 grams / hole. Meanwhile, the optimal dose of urea is used, which is 10 grams / hole.Keywords: Chicken Manure, Urea Fertilizer, Mustard